Synthesis of Benzoxazole-2-carboxylate Derivatives: Electronic- and Position-effect of Functional Groups and Computational Modeling of the Selectivity for Oxazole Ring - ERDEM, SAFİYE (WILEY-V C H VERLAG GMBH, 2021)
In this study, Mitsunobu reagent, DEAD (diethyl azodicarboxylate) and PPh3, and ethyl-oxalamide derivatives of 2-aminophenol were reacted under mild reaction conditions. As a result of the cyclization reaction, benzoxazole derivatives bearing an ester group in the C-2 position were obtained in a one-pot protocol. It was observed that the electron-donating groups at the C-5 position and the electron-withdrawing groups at the C-6 position of the benzene ring increased the yield of the cyclic product. It was found that the cyclization does not occur when the carboxylic acid group is substituted in the benzene ring. The cyclization reaction we performed preferred the 5-endo-trig reaction instead of the 6-exo-trig. This experimental result was examined in detail with density functional theory (DFT) calculations as well. A computational exploration is presented herein that elucidates the detailed mechanism for Huisgen zwitterion's reaction with ethyl-oxalamide derivatives of 2-aminophenol. Potential alternative mechanisms were modeled with DFT calculations via CPCM/M06-2X/6-311++G(d,p)//B3LYP/6-31+G(d,p) level method in tetrahydrofuran to understand shed light on the mechanism. Our computational results are in good agreement with experimental findings that benzoxazole derivatives are the sole products in this reaction.
Keywords: Benzoxazole; 5-exo-trig cyclization; Huisgen zwitterion; Mitsunobu reagent